Motivation, reading and the student - Ediger, Marlow (The RAP Journal, 1990)
Motivation is a rather persitent problem in guiding students to read well. If a student lacks motivation, a low energy level will be available in learning to read. Through motivation, a learner is encouraged to achieve definite goals in reading. With adequately motivated behavior, persistence will aid students in goal attainment.